THE INFLUENCE OF THE HUMIDITY OF THE AIR ON THE CARDIOVASCULAR SYSTEM - Saidova Zilola; Ubaydullayeva Vazira (Journals Park Publishing, 2025)
This article will investigate the effects of different levels of humidity on the circulatory system, including blood pressure, heart rate and general cardiovascular health. As well as analyzing the relationship between air humidity and health indicators related to circulatory system function in order to develop recommendations for the prevention of cardiovascular diseases depending on climatic conditions.
Keywords: Humidity, absolute, relative, cardiovascular system, circulation, blood viscosity, coronary heart disease, hypertension, blood pressure.